Occasional Nominations of the Nominative Field Child in Lesya Ukrainka’s Epistolary Texts (Linguostylistic Studies, 2015)
The register of nominations, forming the nominative field child in Lesya Ukrainka’s epistolary texts, is defined; the main attention is paid to the names with occasional status, most of them were the elements of Kosach-Dragomanov’s family metalanguage with differential nature, being as mean of its brothers and sisters’ – native and cousins (mostly – earlier), and also newhevs’ identification: Maka, Kna-kna, Puts, Putsyk, Putylda, Lyleia, Husia, Husynia, Husynka, Drozd, Drozdyk, Kokh, Kakhota, Patia, Putia, Riuryk, Zoria, Lydyk, Lydianko, Mausyk, Tiusynia, Ymochka, lyleniatko etc.; most of such nominations are applied as general for all or few children, for example, busliata, verchyky, draby, lyseniata, nehry, putsy, tyhry, tyhry-nehry, tyhro-nehry, khrushchyky, shchuchyky; motivation and productive models of stylisticallypaintednominations were defined, first of all individually impressive; the lists of occasional nominations of each child in Kosach family, used in Lesya Ukrainka’s epistolary dialogues, were made more accurate. Key words: occasionalism, nominative field, nomination, lexical regulative, epistolary text, child. References